2021
DOI: 10.9734/jpri/2021/v33i38a32057
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic Regulation with Zinc Combination in Type 2 Diabetes Mellitus

Abstract: Introduction: Zn supplementation improved glutathione peroxidase enzyme activity and decreased malondialdehyde and nitric oxide levels in diabetic rats, revealing Zn's defensive effect against oxidative stress in type 2 diabetes. The investigators have discovered that consuming Zn increased liver function and protected pancreatic tissue from damage caused by diabetes. Since Zn also prevents chronic hyperglycemia, it helps to minimize oxidative stress caused by type 2 diabetes. Diabetes mellitus (DM) is a globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…This shows that persons with low socioeconomic status have misconceptions about how the perimenopause affects women. (36)(37)(38)(39)(40) According to the current study's findings, males should be informed about female perimenopausal syndrome because only the average level (47%) of information about this condition exists among them. (41)(42)(43)(44)(45)(46)(47)(48)(49)(50) Although further study is required, a recent systematic review by Ayers et al found a connection between views and experience (2010).…”
Section: Discussionmentioning
confidence: 82%
“…This shows that persons with low socioeconomic status have misconceptions about how the perimenopause affects women. (36)(37)(38)(39)(40) According to the current study's findings, males should be informed about female perimenopausal syndrome because only the average level (47%) of information about this condition exists among them. (41)(42)(43)(44)(45)(46)(47)(48)(49)(50) Although further study is required, a recent systematic review by Ayers et al found a connection between views and experience (2010).…”
Section: Discussionmentioning
confidence: 82%
“…If surgical option is not available, everolimus may be taken into consideration as an alternative therapeutic option. (13)(14)(15)(16)(17)(18) According to Oesterling et al and Steiner et al the choice of treatment should be based on both tumor size and symptoms According to this approach, tumors >4 cm are frequently symptomatic and have a hemorrhagic tendency, and therefore require either selective embolization or surgical treatments such as partial nephrectomy, enucleation or wedge resection ,whereas tumors < 4 cm should be followed up with yearly CT scans or ultrasonography SAE of renal artery is a safe and effective treatment for symptomatic and large-size AMLS. (9) The therapeutic strategy varies from case to case: selective embolization of the renal artery and surgical removal of the lesion are the pillars of AML management .Alternatively, it is possible to follow the clinical course, with periodic surveillance of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…ANC moms from the AVBR Hospital Sawangi Meghe Wardha are the subjects of section (B), which examines the assessment of maternal and newborn outcomes of oligohydramnios. In section (C), it is discussed how demographic factors and the maternal and newborn outcomes of oligohydramnios in ANC mothers from a particular hospital are related [19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%